NEW SPECIES OF THE GENUS NEPETA (LABIATAE) FROM PAKISTAN - SHINWARI, ZABTA KHAN; CHAUDHRI, MOHAMMAD NAZEER (Biological Sciences - PJSIR, 2022)
A new species of Nepeta, viz., N. gilgitica Shinwari and Chaudhri is described. This species belongs to section Spicatae. Nepeta gilgitica is closley related to N. kokanica Regel.